Real-time X-ray-based 4D image guidance of minimally invasive interventions - Kuntz, Jan; Gupta, Rajiv; Schönberg, Stefan; Semmler, Wolfhard; Kachelrieß, Marc; Bartling, Sönke (European radiology, 2013)
A new technology is introduced that enables real-time 4D (three spatial dimensions plus time) X-ray guidance for vascular catheter interventions with acceptable levels of ionising radiation.